INDONESIA SEBAGAI BENTUK IMPLEMENTASI IDEAL WAWASAN KEBANGSAAN DALAM PENAFSIRAN AL-QURAN - Utomo, Budi; N., Abd. Muid; B, Muhaemin (Institut PTIQ Jakarta, 2023)
The issue of defending the state, which is associated with the choice of the form of the Indonesian nation state, has often sparked fierce debate among Muslim scholars and proponents of the idea of a caliphate state. This writing is motivated by the many political events in Indonesia, which always use this issue as ammunition to force religious ideas and understandings to gain political benefits and support. Thus, the purpose of this presentation is to discuss this issue moderately in the corridor of interpretation of sources of Islamic law through the interpretation of the Quran. This writing method uses historical analysis and analysis of the al-Quran text through relevant interpretations. Ultimately, the researcher found that nationalism in the Qur'an is very close to the idea of Unity in Diversity. The researcher concludes that Indonesia is an ideal form of implementing nationalism, as the Quran desires